25 terminal tips every Mac user should know. - Williams, Jonathan (Mac life)
From customizing your Mac's secret system preferences to remotely controlling another Mac or manipulating text files in a handful of sly ways, the terminal utility is more than just a Mac geek's home base. It's a place where, with a few expert tricks, all Mac users can feel right at home.